1993
DOI: 10.1287/opre.41.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Improved Algorithms for Economic Lot Size Problems

Abstract: Many problems in inventory control, production planning, and capacity planning can be formulated in terms of a simple economic lot size model proposed independently by A. S. Manne (1958) and by H. M. Wagner and T. M. Whitin (1958). The Manne-Wagner-Whitin model and its variants have been studied widely in the operations research and management science communities, and a large number of algorithms have been proposed for solving various problems expressed in terms of this model, most of which assume concave cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
197
0
6

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(204 citation statements)
references
References 37 publications
1
197
0
6
Order By: Relevance
“…Corresponding to each candi-date, the first t period problem is a deterministic ULS with a given final inventory level, which is equivalent to another ULS without final inventory by updating the demand at time period t. Thus, the optimal solution can be obtained in O(n log n) time as studied by Aggarwal and Park (1993).…”
Section: Propositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corresponding to each candi-date, the first t period problem is a deterministic ULS with a given final inventory level, which is equivalent to another ULS without final inventory by updating the demand at time period t. Thus, the optimal solution can be obtained in O(n log n) time as studied by Aggarwal and Park (1993).…”
Section: Propositionmentioning
confidence: 99%
“…A simple dynamic programming algorithm based on this property runs in O(T 2 ) time, where T is the number of time periods; this was improved later to O(T log T ) or linear time for the case in which the costs exclude speculative motives (for details see Aggarwal and Park (1993), Federgruen and Tzur (1991), and Wagelmans et al (1992)). Polynomial time algorithms have also been developed for variants of the deterministic ULS.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, three important papers, Aggarwal andPark (1993), Federgruen andTzur (1991), and Wagelmans et al (1992), improved the time complexity for obtaining an optimal solution from O(T 2 ) to O(TlogT) for general problems, and to O(T) for problems with a special cost structure. For interesting generalizations of Wagner and Whitin's model, see Bitran et al (1984), Chen et al (1994), Lee (1995), Chung andLin (1988), Florian et al (1980), Wagelmans (1996, 1997), Lee (1989), Lee and Denardo (1986), Maes and Van Wassenhove (1985), Swoveland (1975), andZangwill (1966).…”
Section: Problem Motivations and Related Literaturementioning
confidence: 99%
“…Remark 1: Recently, Federgruen and Tzur (1991), Wagelmans et al (1992), and Aggarwal and Park (1993) have developed O(T) algorithms to solve the classical dynamic lot-sizing problems for which n ≤ T. One of the key ideas in those papers is to transform the mathematical formulation of the classical dynamic lot-sizing model to an equivalent formulation without holding costs. Unfortunately, for the more general problem with demand time window considerations, equation (4) seems to make such a transformation difficult.…”
Section: Recall That the Computational Complexity Of Calculating B(smentioning
confidence: 99%
“…Florian et al (1980) have in fact shown that even the single-item case N = 1 is NP-complete, as opposed to the uncapacitated version that, for a planning horizon of T periods, is solvable in O T log T time (see Federgruen and Tzur 1991, Wagelmans et al 1992, and Aggarwal and Park 1993, and in O T time under some mild assumptions on the data. The difficulty arises in part because under capacity restrictions, it may no longer be optimal to place an order at the last possible time; in other words, it is not possible to confine oneself to so-called zero-inventory ordering policies.…”
Section: Introductionmentioning
confidence: 99%